Navigating the intersection between postponement strategies and additive manufacturing: insights and research agenda - Prataviera, Lorenzo Bruno; Jazairy, Amer; Abushaikha, Ismail (Taylor & Francis, 2026)
Postponement is a popular principle used to improve supply chain responsiveness and increase customisation by delaying manufacturing and logistics operations until more accurate market demand information is available. In business environments where responsiveness and customisation are increasingly important, additive manufacturing (AM) has recently emerged as a high-potential manufacturing technology. Due to changes in customer behaviours that affect product life cycles and variety, AM could disrupt traditional manufacturing and greatly impact postponement decisions. However, the intersection between postponement and AM is largely underexplored. This study aims to investigate the intersection between postponement and AM to meet the escalating demand for customised products. We conceptualise opportunities and challenges related to when customisation is introduced, concerning the positioning of the customer order decoupling point and to where customisation takes place, as operations could shift across supply chain tiers or even jurisdictions. By shedding light on the intersection of postponement and AM and its implications for customisation, this study formulates a research agenda focusing on five main postponement improvement dimensions: uncertainty, volume, lead time, supply chain design, and environmental sustainability. Moreover, it formalises a set of managerial implications to pragmatically foster the strategic implementation of AM across different postponement scenarios.
Special Issue: Human-centric artificial intelligence-empowered smart design and manufacturing towards Industry 5.0
Keywords: postponement; addictive manufacturing; customisation; 3D printing; supply chain; conceptual